Memahami Konsep Keselamatan dan Filsafat Kristen Tinjauan Dari Perspektif Teologis Dan Filosofi - Setulus Hati Laia; Mozes lawalata (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
On the other hand, from a Christian philosophical perspective, the concept of salvation can be approached through rational thinking and conceptual analysis. Christian philosophy often explores ontological and epistemological questions about the nature of salvation, such as the relationship between human freedom and God's sovereignty, as well as the nature of spiritual truth. This research highlights the differences in sources of authority, methods of truth discovery, and ultimate goals between theological and philosophical approaches to salvation. While theology relies on religious teachings, divine revelation, and religious experience, Christian philosophy tends to use logical reasoning and conceptual analysis. However, these two fields can complement each other in deepening understanding of the concept of salvation, creating creative and in-depth dialogue about the nature of the Christian faith. This research provides valuable insights for theologians, philosophers, and practitioners of Christianity to explore the concept of salvation holistically, combining deep theological understanding with critical philosophical analysis.